Identification of incident factors in the adoption decisions of technology in family cattle producers breeders - Molina, C.; Alvarez, J. (Agrociencia Uruguay, 2009)
Beef cattle production is a sector of great importance for the national economy. The cattle stagnation has been studied for a long time. In the last years, productivity indicators have been increasing. The sector to the bovine breeder, is the sector that has shown smaller levels of improvement. Within the same one, the small and medium familiar livestock farmer constitute an important number of producers, and conforms the majority of the rural settlers of Uruguay. The study identify the factors that affect the adoption decisions of technology, from the point of view of this producers. Were made a studies of case, with 9 (nine) participant producers of a project named «Integrando Conocimiento» of the Plan Agropecuario. The field work of field was conducted between the months of October and December of 2006. It was visited the selected producers and one asked of direct way about which they did and the reasons to them that they had for it. Were identified an important number of factors that affect the adoption decisions and non adoption. This study made possible in addition raising ideas for the design of intervention strategies, with the objective to obtain a greater development of this one type of producers.